2014
DOI: 10.3390/w6061771
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of Water Consumption and Its Effects on Water Conservation Behavior

Abstract: Abstract:The usual perception of consumers regarding water consumption is that their bills do not match their actual water consumption. However, this mismatch has been insufficiently studied; particularly for cases related to specific water-use patterns, water conservation practices, and user socio-demographics. In this study, a total of 776 households in 16 villages situated in the rural Wei River Basin are investigated to address the gap in the literature. Questionnaires and 3-day water diaries are used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
5
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 25 publications
4
48
5
5
Order By: Relevance
“…Hence, our results suggest that greater awareness and understanding of the WF concept, which represents a key-factor affecting water saving behaviors, could favor sustainable water consumption and management (cf. [80]). …”
Section: Discussionmentioning
confidence: 99%
“…Hence, our results suggest that greater awareness and understanding of the WF concept, which represents a key-factor affecting water saving behaviors, could favor sustainable water consumption and management (cf. [80]). …”
Section: Discussionmentioning
confidence: 99%
“…Attari (2014) investigated perceptions of water-use and found improving the public's understanding of their personal wateruse can impact strategies geared towards the adoption of water-saving practices. Fan, Wang, Liu, Yang, & Qin (2014) found significant associations between resident perceptions of personal wateruse and actual water-use. Particularly, residents underestimated their outdoor water-use and overestimated the amount of water consumed indoors.…”
Section: Theoretical Frameworkmentioning
confidence: 86%
“…Only 12% of the students reported home water bills of less than 500 AED, while 57% reported water bills higher than 500 AED and about 31% did not know what the water bill was for their residences. A previous study showed that residents with high income and education levels easily underestimate their own use [34]. The members of this group consume more water than those of other groups and are not concerned about their water bills, leading them to underestimate their water use [34].…”
Section: Understanding Student Water Use Habits On the Uaeu Campusmentioning
confidence: 95%
“…A previous study showed that residents with high income and education levels easily underestimate their own use [34]. The members of this group consume more water than those of other groups and are not concerned about their water bills, leading them to underestimate their water use [34]. Therefore, there is a need for greater public awareness among families and their children regarding the financial and environmental costs of water.…”
Section: Understanding Student Water Use Habits On the Uaeu Campusmentioning
confidence: 99%